Welfare Considerations in Migration Decision-Making through a Life-Course Approach: A Qualitative Study of Spanish EU-Movers - Andrejuk, Katarzyna; Godin, Marie; Jolivet, Dominique; Pereira, Sónia; Van Mol, Christof (Central and Eastern European Migration Review, 2021)
The welfare aspects of intra-European migration remain an important and controversial topic of academic and political debates. These discussions touch upon the classical ‘welfare magnet’ or ‘welfare tourism’ hypothesis. Transcending the politicised concept of ‘benefit tourism’, our paper examines how welfare-state considerations in relation to migration decisions vary across the life course. Relying on micro-level qualitative research focusing on Spanish intra-EU movers, the paper probes deeper into how individuals perceive welfare systems, analysing the subtle and nuanced meanings of different aspects of the welfare for their migration decisions. We focus more specifically on welfare provisions in terms of health care, compulsory education, child support and other care responsibilities, unemployment and pensions and retirement. Our research indicates that, in studies on the migration–welfare nexus, it is necessary to move beyond the current narrow focus on the welfare magnet hypothesis and to examine how diverse welfare arrangements continuously and dynamically set the context for migration decisions at various stages of an individual’s life. The results of our research show how features of the Spanish welfare system, in comparison to those of potential destination countries, might act as both a trigger and/or a barrier to migration. As such, we get a ‘thicker description’ of the role which welfare might play in shaping individuals’ eventual migratory aspirations and decisions.
Keywords: crisis; migration aspirations; migration decisions; Spain; welfare magnet; welfare state